Determinants of Adherence to Antiretroviral Therapy in HIV/AIDS Patients in Jambi - Nurhaida Sigalingging; Rico Januar Sitorus; Rostika Flora (Media Kesehatan Masyarakat, 2022)
Every HIV/AIDS sufferer is expected not to forget to take medication more than 3 times a month with the number of ARV drugs that must be taken is 60 times. Non-adherence in taking ARV drugs can cause resistance effects so that the drugs will not work or will fail, so it is hoped that PLWHA will comply with taking ARV drugs. There are several factors that affect patient compliance in undergoing antiretroviral therapy (ARV). The purpose of this study was to analyze the determinants of adherence to taking ARV drugs in patients with HIV/AIDS in Jambi City. This study is an analytic observational study with a cross-sectional approach. Sampling using purposive sampling. The sample in this study were 235 people with HIV/AIDS who were taking ARV therapy. The results of this study indicate that there is a relationship between respondents' knowledge and adherence to ARV drugs, there is no relationship between attitudes and adherence to taking ARV drugs, there is a relationship between actions and adherence to taking ARV drugs, there is no relationship between age and adherence to taking ARV drugs, there is no relationship between sex and adherence to ARV drugs. adherence to taking ARV drugs, there was no relationship between education and adherence to taking ARV drugs, there was a relationship between family support and adherence to taking ARV drugs, and there was no relationship between length of treatment and adherence to taking ARV drugs. Health facilities are confounding in the relationship between attitudes, knowledge and actions with ARV drug adherence in PLWHA. A sustainable HIV/AIDS control program is needed for public awareness or socialization about the need for support for PLWHA to comply with ARV consumption.